Appliance Of Rapd Markers In The Analysis Of Genetic Variations In Five Mango Cultivars (Applied Biological Research, 2019)
The aim of this work was to analyze molecular relationship between five  mango (Mangifera indica) cultivars viz., ‘Alphanso’, ‘Totapuri’, ‘Langra’,  ‘Kesar’ and ‘Amrapalli’ using molecular RAPD markers. In present study,  genomic DNA isolation procedure was standardized to extract DNA from  mango pulp. All the samples tested yielded good quality DNA as 260/280 nm  ratio was within 1.6-1.8 range revealing that no significant amount of  proteins was present in extract. The statistical analysis (ANOVA) indicated p  ≤0.05 validating the applicability of optimized protocol. The extracted DNA  was subjected to PCR with 39 primers. Thirty six RAPD primers produced  distinct and consistent RAPD profiles which revealed 160 bands with decent  87% polymorphism. Neighbour joining tree, constructed based on Nei’s  genetic distance, displayed splitting of tested cultivars into two separate clades  designated as I and II. The method employed in this study highlighted the  reproducibility of technique and, therefore, appears to be a useful tool for  genetic analysis in mango and other related plant species.
Keywords: DNA; mango cultivars; PCR; phylogenetic tree; RAPD